P-4 Canine recurrent pyoderma: a multicenter prospective study - Bensignor, E.; Germain, P. A. (Veterinary dermatology, 2004)
Bacterial pyoderma is one of the most frequent skin diseases in dogs. Recurrent pyoderma is often secondary to an underlying skin disease, but no epidemiological study has been published on the subject to the authors’ knowledge. This study was designed to prospectively evaluate the causes responsible for recurrent pyoderma in dogs. Dogs presenting with a history of more than three episodes of skin infection in the last year were included in the study. For each case, epidemiological and clinical data were collected. Pyoderma was confirmed by the clinical signs, the demonstration of bacteria on microscopic examination of cytological smears and a positive culture. Each animal was treated with an appropriate course of antibiotics until resolution of signs of pyoderma. Depending upon the presence of pruritus, appropriate diagnostic tests were performed: skin scrapings, acaricidal trial, flea treatment, elimination diet, intradermal testing, biopsies, endocrinological tests, leishmaniasis and ehrlichiosis serology, antinuclear antibody testing. Thirty dogs (14 males and 16 females) of 19 different breeds, aged from 1 to 12 years (mean 4.9 years) were included. Diagnosis was folliculitis (44%), folliculitis and furunculosis (20%), furunculosis (20%), cellulitis (10%). Staphylococcus intermedius was isolated in 97% of cases. The following underlying diseases were identified: atopic dermatitis (60%), food allergy (7%), flea allergy (7%), hypothyroidism (7%), hyperestrogenism (4%), demodicosis (4%), and zinc‐responsive dermatosis (4%). In two dogs, no underlying cause could be identified. Atopic dermatitis is the most common disease associated with recurrent pyoderma in dogs. Funding: Pfizer Animal Health.